Didactic Audiovisual Translation in Online and Face-to-face Class Environments. : A Comparative Study - Gonzalez-Vera, Pilar; Couto-Cantero, Pilar; Fraga-Castrillón, Noemi (Íkala, Revista de Lenguaje y Cultura, 2025)
This article provides further empirical validation of the tradilex didactic audiovisual translation methodology across diverse learning frameworks and educational contexts by means of a quantitative and comparative study. The scope was extended to multiple settings across Spain, by targeting a sample of 566 non-native English-speaking participants from eight Spanish higher education institutions, from which 155 completed 15 intermediate-level English lesson plans. The statistical analysis was conducted using SPSS software and an anova test, examining the results based on whether the lesson plans were implemented in face-to-face or online class environments. The results show how the learners’ language skills developed under the two modalities using five audiovisual translation methods, thus proving the validity of didactic audiovisual translation in Englishas-a-foreign-language teaching and learning. The tradilex methodology has proven effective in enhancing overall communicative competence, as evidenced by the findings of this study. Notably, no statistically significant differences were observed between online and face-to-face instructional modalities, suggesting that both environments facilitate successful language learning. These results contribute to the ongoing discourse on pedagogical effectiveness, providing valuable insights that may inform best practices and further empirical investigations in the field of applied linguistics and language education.